MANOEL DE BARROS: AS CORES DA INFÂNCIA - Campos, Hélvio Henrique de (2014)
The current dissertation follows the Reading and interpreting poetics line of research, intending to analyze the work of the poet from Mato Grosso, Manoel de Barros, under a poststructuralist theoretical perspective, with the purpose to identifying the child point of view, that no experiences has been accumulated yet, whereas as a means to increasing the word ability possibilities. Recurrently, the theme in case has been showed on Barros’s verses, thus there are the children’s behavior, vision and way of doing things in his poetic construction. Because of that, the expression of his poetry will figure as a usual return to the unformed beginning of life, the childhood. To elect this exposed theme, two theoretical lines had been chosen to connect the pieces that were doubtful observed on Manoel de Barros’s work: some literary space Maurice Blanchot’s considerations and Giorgio Agamben’s reflection about childhood, the language test and the experience destruction, becoming them linked with others writers.